Food allergies in rural areas - Stoma, Monika; Ślaska-Grzywna, Beata; Żukiewicz-Sobczak, Wioletta A.; Kostecka, Małgorzata; Bojanowska, Monika; Dudziak, Agnieszka; Kuna-Broniowska, Agnieszka; Adamczuk, Piotr; Sobczak, Paweł; Andrejko, Dariusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: A food allergy is a group of symptoms occurring in the organism and resulting from consuming some food, where the problems are conditioned by immunological mechanisms. The symptoms may become apparent first in adulthood and they may be an initial manifestation of a latent allergy. Typical symptoms of a food allergy occur in different organs, thus not only in the digestive system, but also in the skin, respiratory system and circulatory system. Aim: To assess the frequency of food allergy onset in rural areas of the Lublin region as well as to determine which factors induce such allergies. Material and methods: A survey was conducted, involving the participation of 340 inhabitants of rural areas. The study monitored the knowledge and situation of the disease, concerning allergens, allergy symptoms, methods of treatment and opinions regarding such treatment. Results : The analysis focused on 124 people with diagnosed allergies. Conclusions : Introducing a diet did not result in a statistically significant difference regarding elimination of the symptoms, as compared to the patients who did not follow any diet. On the other hand, pharmacological treatment causes statistically worse results than using other methods or not being treated at all. The patients in whom allergy symptoms disappeared were more convinced about the positive character of their diet than those in whom the symptoms were not eliminated. The age when the allergy becomes evident does not affect its duration, yet it matters as to the time of its later elimination. The more symptoms were experienced by a patient, the longer the duration of the allergy was.